Family members' experiences of assisted dying: A systematic literature review with thematic synthesis. (September 2019) - Gamondi, Claudia; Fusi-Schmidhauser, Tanja; Oriani, Anna; Payne, Sheila; Preston, Nancy
Background: Families' experiences of assisted dying are under-investigated and families are rarely considered in clinical guidelines concerning assisted dying. Aim: To systematically review family experiences of assisted dying. Design: A systematic literature review using thematic synthesis. Data sources: MEDLINE, Embase, CINAHL, AMED (Allied and Complementary Medicine) and PsycINFO databases (January 1992 to February 2019). Studies investigating families' experiences on the practice of legalised assisted dying were included. We excluded studies prior to legalisation within the jurisdiction, secondary data analysis and opinion papers. Results: Nineteen articles met the inclusion criteria. Publications were derived from four countries: The Netherlands, United States (Oregon, Washington and Vermont), Canada and Switzerland. Dutch studies predominately investigated family involvement in euthanasia, while Swiss and American studies only reported on assisted suicide. Eleven studies had a qualitative design, using predominately in-depth interviews; seven were retrospective surveys. Five analytical themes represented families' experiences in assisted dying: (1) context of the decision, (2) grounding the decision, (3) cognitive and emotional work, (4) experiencing the final farewell and (5) grief and bereavement . The results showed that families can be very involved in supporting patients seeking assisted dying, where open communication is maintained. Family involvement appeared to be influenced by the type of legislation in their country and the families' perception of the social acceptability of assisted dying. Conclusion: Our data confirm that families across all jurisdictions are involved in assisted suicide decision and enactment. Family needs are under-researched, and clinical guidelines should incorporate recommendations about how to consider family needs and how to provide them with evidence-based tailored interventions.